Review of the UPFC Different Models in Recent Years - Mahmoud Zadehbagheri; Rahim Ildarabadi; Majid Baghaei Nejad (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
Unified Power Flow Controller (UPFC) is one of the most intriguing and, potentially, the most versatile classes of Flexible AC Transmission Systems (FACTS) devices. The UPFC is a device which can control simultaneously tree parameters line impedance, voltage, phase angle and dynamic compensation of AC power system. In order to analyse its true effects on power systems, it is important to model its constraints, due to various ratings and operating limits. This paper reviews on the different models of UPFC used in recent years and gives sets of information for each model of the UPFC in AC transmission. Then the different models are compared and features of each model are examined.DOI: http://dx.doi.org/10.11591/ijpeds.v4i3.5982